Floristic-Functional variation of tree component along an altitudinal gradient in araucaria forest areas, in southern Brazil - Soboleski V.F.* (2017)
© 2017, Academia Brasileira de Ciencias. All rights reserved.We aimed to investigate the taxonomic and functional variations of tree component of Araucaria Forest (AF) areas located along an altitudinal gradient (700, 900 and 1,600 m asl), in the southern region of Brazil. The functional traits determined were leaf area, specific leaf area, wood density, maximum potential height and dispersal syndromes and deciduousness. The data were analyzed through a functional and taxonomic dissimilarity dendrograms, community-weighted mean trait values, parametric and nonparametric tests, and Principal Component Analysis. The largest floristic-structural similarity was observed between the lower altitude areas (700 and 900 m asl), whose Bray-Curtis distance was 0.63. The area at 700 m asl was characterized by a predominance of deciduous and semi-deciduous species, with a high number of self-and wind-dispersed species, whereas the area at 1,600 m asl exhibited a predominance of animal-dispersed and evergreen species. It was also observed that there were significant variations for leaf traits, basic wood density and maximum potential height. Over all altitudinal gradient, the ordinations indicated that there was no evidence of functional differentiation among dispersal and deciduousness groups. In conclusion, the evaluated Araucaria Forest areas presented high floristic-functional variation of the tree component along the altitudinal gradient.